Pengaruh Pengembangan Talenta terhadap Kepuasan Kerja, Kinerja Tugas, dan Komitmen Afektif dengan Mediasi oleh Keadilan Distributif dan Moderasi Keadilan Prosedural - Fauziah, Ika Mulatsih; Rachmawati, Riani (UI Scholars Hub, 2021)
The challenges of the Indonesian economy are currently increasingly complex, so the role of the financial industry regulator is very important because the policies taken have an effect to all people and the credibility of the government. In carrying out this role, competent employees are needed so it must be ensured that employee development through talent development is carried out with good planning and strategy. The application of talent development and perceptions of employee fairness can affect job satisfaction, task performance, and affective commitment. This research purposes to determine the impact of talent development implementation on job satisfaction, task performance, and employee affective commitment with distributive justice as a mediator and procedural justice as a moderator in the Indonesian Financial Industry Regulatory Institution (LARIK) with structural equa- tion modeling. The research data were obtained from 464 LARIK employees using an online ques- tionnaire. Research has found that talent development has a positive effect on job satisfaction, task performance, and affective commitment. Research also reveals that distributive justice mediates this partial effect. Another result is procedural justice moderating the relationship of distributive justice to job satisfaction, task performance, and affective commitment. Next, the managerial and practical implications of these findings are discussed.